The genus Hyboella Hancock (Orthoptera: Tetrigidae: Metrodorinae) in China - Deng, Wei-An; Zheng, Zhe-Min; Wei, Shi-Zhen (Zootaxa, 2009)
The species of Hyboella Hancock occurring in China are listed. Two new species, Hyboella tuberdoralis sp. nov. and Hyboella jiuwanshanensis sp. nov. are described. The synonymy, distribution and a key to the species are presented.